Social media use intensity at workplace among human resources executives of a government agency headquarters in Kuala Lumpur, Malaysia / Nurhamizah Binti Ishak, Farah Nadzirah Khairuddin and Nur Shaziella Aziz - Ishak, Nurhamizah; Khairuddin, Farah Nadzirah; Aziz, Nur Shaziella (2020)
Browsing social media is a common daily activity for most people all around the globe nowadays regardless of age and gender. Although the frequency, duration and motive of browsing social media differs from one person to another, the existence of employees who have social-media mania and keep browsing social media all the time even during their working hours causes the employers to monitor their employees' social media use intensity at workplace from time to time. This study looks at the level of social media use intensity at workplace among Human Resources executives of a government agency headquarters in Kuala Lumpur, Malaysia. Questionnaires were used to collect data on the sample. Due to its quite small population size, total population sampling method is applied. Out of 68 executives, only 30 completed the questionnaires (response rate = 44.12%). Findings revealed that the sample have high level of social media use intensity at workplace. However, there was no statistically significant difference between social media use intensity and gender. Other than that, it was found that the main motive behind using social media at workplace is interpersonal. As for the implications of this study, it contributes to the corpus of knowledge in the area of social media use intensity at workplace in local organization context and provides empirical data to assist organization in conducting appropriate policy to control social media use intensity at workplace among their employees.